Climate change and plants : biodiversity, growth and interactions - Fahad, Shah (Assistant professor of agriculture) (Boca Raton : CRC Press, 2021)
"Evidence raises every day of the varying climate and its impression on both plants and animals. Climatic changes influence all the agriculture factors, which can potentially adversely affect their productivity. Plant activities are intimately associated to climate and concentration of atmospheric carbon dioxide. The book Climate change and Plants Interactions: Complexities and Surprise examines how plant growth characters influences/influenced by the climate change both in past and present scenarios. The book cover papers present the cutting-edge research in key determinates of plant growth in response to atmospheric CO2 enhancement and global warming. Salient Features Discourses numerous goals of sustainable development goals projected by the UN as part of the 2030 agenda. Highlights the appropriate approaches for maintaining better plant growth under changing climatic conditions Presents diversity of techniques used across plant science. Design to cater to the needs of researchers, technologists, policy makers and undergraduates and postgraduates' students studying, sustainable crop production, crop protection. Addresses plant responses to atmospheric CO2 increase"--
Includes bibliographical references and index.
Keywords: Vegetation and climate; Plant-atmosphere relationships; Climatic changes